2022
DOI: 10.1038/s41598-022-15040-w
|View full text |Cite
|
Sign up to set email alerts
|

Spectral organ fingerprints for machine learning-based intraoperative tissue classification with hyperspectral imaging in a porcine model

Abstract: Visual discrimination of tissue during surgery can be challenging since different tissues appear similar to the human eye. Hyperspectral imaging (HSI) removes this limitation by associating each pixel with high-dimensional spectral information. While previous work has shown its general potential to discriminate tissue, clinical translation has been limited due to the method’s current lack of robustness and generalizability. Specifically, the scientific community is lacking a comprehensive spectral tissue atlas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 66 publications
0
17
0
Order By: Relevance
“…Hyperspectral Imaging (HSI) is a fast and noninvasive and nonionizing monitoring technique based on spectrometric tissue analysis (88)(89)(90). The target tissue is illuminated by halogen lamps and remitted light is detected in a wavelength spectrum from visual to near-infrared light (380-1000 nm) (91).…”
Section: Hyperspectral Imagingmentioning
confidence: 99%
“…Hyperspectral Imaging (HSI) is a fast and noninvasive and nonionizing monitoring technique based on spectrometric tissue analysis (88)(89)(90). The target tissue is illuminated by halogen lamps and remitted light is detected in a wavelength spectrum from visual to near-infrared light (380-1000 nm) (91).…”
Section: Hyperspectral Imagingmentioning
confidence: 99%
“…DL is currently often utilized in image recognition, a process summarized by the term radiomics. [5][6][7][8] With the rise of minimally invasive pancreatic surgery (MIPS), intra-and postoperative patient data are becoming increasingly available for AI applications. The vast amount of generated data open a rapidly growing new field for AI supported decision-making, surgical training, image guidance, and personalized postoperative management.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperspectral imaging (HSI) is a novel technique in medical imaging. In previous publications it has already been shown that HSI has the ability to record organ-speci c spectral re ectance (4) and that it has the ability to evaluate changes in microcircular capillary perfusion of tissue in porcine models (4). It has now been used to assess the quality of microcirculatory perfusion in critically ill patients (5).…”
Section: Introduction Backgroundmentioning
confidence: 99%